¿Inestabilidad en el lado oscuro? estructura factorial, invarianza de medición y fiabilidad de la Dirty Dozen Dark Triad en población general de Lima - Copez Lonzoy, Anthony; Dominguez-Lara, Sergio; Merino-Soto, César (Revista de Psicopatología y Psicología Clínica, 2020)
Abstract: Instability on the dark side? Factorial structure, measurement invariance and reliability of the Dirty Dozen Dark Triad in the general population of Lima. The dark triad of the personality is a complex measure composed of three traits such as Machiavellianism, psychopathy and narcissism that are associated with destructive behaviors to the interests of others. The Dirty Dozen Dark Triad (DDDT) scale was used to evaluate the dark triad. The present study seeks to analyze the internal structure, measurement invariance and reliability of DDDT scores. 320 people were recruited (64.1% women), the average age was 24.4 and 89.7% were single. Four measurement models were identified by means of confirmatory factor analysis; the measurement invariance was also evaluated, which did not show a significant deterioration for the group according to gender. In addition, congeneric and tau-equivalent models were implemented and the accuracy of the scores for all the factors was > .70. This DDDT version provides useful evidence at the psychometric level to be implemented with a screening instrument in the psychological evaluation. Keywords: Dirty Dozen Dark Triad; validation; measurement invariance; personality. Resumen: Las triada oscura de la personalidad es una medida compleja compuesta de tres rasgos como maquiavelismo, psicopatía y narcisismo que están asociados a comportamientos destructivos a los intereses de los demás. Para evaluar la tríada oscura fue utilizada la escala Dirty Dozen Dark Triad (DDDT). El presente estudio busco analizar la estructura interna, invarianza de medida y la fiabilidad de las puntuaciones de la DDDT. Fueron reclutados 320 personas (64.1% mujeres), el promedio de edad fue 24.4 y el 89.7% fueron solteros. Se identificados cuatro modelos de medida mediante análisis factorial confirmatorio, también fue evaluada la invariancia de medida que no evidencio un deterioro significativo para el grupo según género. Además, fueron implementados modelos congenéricos y tau-equivalentes y la precisión de las puntuaciones para todos los factores fue >.70. Esta versión DDDT reporta evidencias útiles a nivel psicométrico para ser implementadas como instrumento de despistaje en la evaluación psicológica. Palabras clave: Dirty Dozen Dark Triad; validación; invarianza de medición; personalidad.